Fit between applicants' prior knowledge and university selection criteria: study of Finnish teacher education student admission in 2013–2015. Issue 2 (15th March 2023) - Kunnari, Jenni; Pursiainen, Jouni; Läärä, Esa; Rusanen, Jarmo; Muukkonen, Hanni
ABSTRACT: Fluent transitions to higher education are a common concern, especially in highly selective Finnish teacher education (TE). This study examined the fit between the matriculation examination (ME) results and the selection criteria applied in TE. We studied the accepted applicants in Finland in 2013–2015 (n = 5116), and both the accepted and rejected applicants at the University of Oulu in 2015 (n = 2170). Among the accepted applicants, the ME typically consisted of mother tongue, advanced syllabus English, basic syllabus mathematics, psychology, and health education. The various selection criteria did not directly differentiate the applicants with respect to the ME. The two strongest predictors in the ME for acceptance to TE were the choice of and performance in advanced syllabus mathematics and psychology. The results are discussed in light of selection criteria and TE.